ANALISIS DAN PENERAPAN PENDIDIKAN DASAR SEBAGAI PROSES MORALISASI - Putri, Riska Nanda; Nada, Annisa Qathratun; Desyandri, Desyandri; Jamaris, Jamaris (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The issue of moral degradation in Indonesia is an important problem for the educational world. Until now, schools are considered to be part of the responsibility for creating a better future generation. Primary school as an institution becomes the initial foundation in moral cultivation. How the primary schools provide learning experiences to their students and the role of the teacher in the learning process in elementary school greatly determines the student’s future. To achieve those moral education successfulness, the moral education in the basic education should be proceed with a comprehensive learning method. Furthermore, a good classroom environment also become the key point for moralizing process accompishment.